Iraq's official position on internal political developments in Türkiye (1925-1932 AD) (Journal of the College of Basic Education, 2024)
Historians have been interested in Turkiye's contemporary history, Especially in Iraq .This is Due to geographical proximity relations which connect between Iraq and Turkiye . As well as the political ,economic and social relations , attention of Iraq also been directed to study the internal and external developments during the contemporary history of Turkey. There are a political figures made an important role in the public life of Turkey, and several factors that led to make the Kurdish revolution 1925 . this uprising had an opinion that was expressed through the Turkish government's policy and procedures against the Kurdish civilians .These internal political developments was found during (1925-1932) it had a great influence in Iraq. It has that period a lot of events and important developments that Iraq focused on it . Iraq also has a role and position from these internal political developments in Turkey in order to avoid making mistakes that Turkey fell into .